Biogeographic history and diversification patterns in the Irano-Turanian genus Acanthophyllum s.l. (Caryophyllaceae). (4th May 2021) - Mahmoudi Shamsabad, Masoumeh; Moharrek, Farideh; Assadi, Mostafa; Nieto Feliner, Gonzalo
Abstract: The Irano-Turanian (IT) floristic region in Asia contains three biodiversity hotspots and has been a source of xerophytic taxa for neighboring regions. Despite its species richness and large territory, the evolutionary history and biogeography of this floristic region is poorly understood. Acanthophyllum, encompassing ca. 70 subshrubby mostly thorny-cushion species, is one of the important components of the steppe and mountain vegetation of this region. In this study, we investigate the tempo and mode of diversification as well as the biogeographic patterns of this genus. The ancestral area analysis suggests that Acanthophyllum originated east of the Zagros Mountains in the Miocene, from where it expanded westwards. A shift in the speciation rate in the late Pliocene (ca. 3.24 Ma) was detected, based on a nrDNA ITS tree, affecting the lineage of the largest section in the genus, Acanthophyllym sect. Oligosperma . Parallelisms with another IT species-rich genera in aspects such as largely coincident ranges and habitats, presence of a thorny-cushion life-form, similar areas reconstructed for their MRCA, and the inference of a shift in speciation in the region suggest common underlying abiotic and biotic factors or even drivers for diversification and speciation in the high elevation dry continental landscape of IT region.